Tagger's delight? Disclosure and liking behaviour in Facebook: the effects of sharing photographs amongst multiple known social circles - David Houghton; Adam N. Joinson; Nigel Caldwell; Ben Marder (University of Birmingham, Birmingham Business School, 2013)
The present work identifies the relationship between sharing photographs with different depictions in Facebook on relationship quality, which varies depending on the type of target sharing the photographs. With over 1 billion active users, disclosure on Facebook is frequent, considered a norm of online interaction, and actively encouraged by site providers. The extant academic literature identifies Facebook as an effective tool to connect with known and unknown others, and identifies the differences in sharing behaviour when users are aware of their audience. Operating within a lowest common denominator approach to disclosure on Facebook, the present work identifies the potential consequences to personal relationships when sharing day-to-day information. Results found from a sample of 508 Facebook users suggests individuals should actively adjust their privacy settings to ensure that even amongst flattened information - i.e. that deemed appropriate for release to all target types - disclosure does not harm current and potential relationships. Implications for, users, academic theory and disclosure practice are discussed.
Keywords: 650; Facebook; personal relationships; sharing behaviour